An out-of-band mobile authenticating mechanism for controlling access to data outsourced in the mobile cloud environment. (30th October 2019) - Yadav, Sumit Kumar; Saroha, Nisha; Sharma, Kavita
'Mobile Cloud Computing' (MCC), a cloud environment, formed by mobile users at the client-side and cloud servers at the back-end enables users to store and pervasively access a huge amount of data via different mobile devices in a distributive manner. This increases the risk of data abuse, since data is outsourced on the distrusted cloud servers. The drawbacks of the current frameworks, such as overloaded computations in key distribution, reduced flexibility, and scalability, are unable to achieve fine-graininess and confidentiality. Thus, we propose an 'access control mechanism' which is lightweight with minimal computational overhead and provides fine-grained access control for sharing data using out-of-band (OOB) mobile authentication. Here we perform client-side encryption and decryption using simple hash functions and concatenation operator and achieve dynamic scalability. The encryption algorithms, sharing mechanism, and the use of OOB mobile authentication are extensively analysed to prove its efficiency and applicability.